2011
DOI: 10.1093/nar/gkr985
|View full text |Cite
|
Sign up to set email alerts
|

A supramolecular assembly formed by influenza A virus genomic RNA segments

Abstract: The influenza A virus genome consists of eight viral RNAs (vRNAs) that form viral ribonucleoproteins (vRNPs). Even though evidence supporting segment-specific packaging of vRNAs is accumulating, the mechanism ensuring selective packaging of one copy of each vRNA into the viral particles remains largely unknown. We used electron tomography to show that the eight vRNPs emerge from a common ‘transition zone’ located underneath the matrix layer at the budding tip of the virions, where they appear to be interconnec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

18
218
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 155 publications
(237 citation statements)
references
References 35 publications
(104 reference statements)
18
218
1
Order By: Relevance
“…They are composed of three long RNPs and five shorter RNPs of significantly different lengths, suggesting that the eight RNPs contain at least six different kinds of viral RNA segments (13,14). Interestingly, ET also suggests that the eight RNPs within a virus particle are connected to each other, forming a supramacromolecular complex (12,13). This observation is consistent with reverse genetics studies demonstrating that mutations in a packaging signal of a viral RNA segment affect the packaging efficiency of the other viral RNA segments in the progeny virus particles (15).…”
supporting
confidence: 79%
See 1 more Smart Citation
“…They are composed of three long RNPs and five shorter RNPs of significantly different lengths, suggesting that the eight RNPs contain at least six different kinds of viral RNA segments (13,14). Interestingly, ET also suggests that the eight RNPs within a virus particle are connected to each other, forming a supramacromolecular complex (12,13). This observation is consistent with reverse genetics studies demonstrating that mutations in a packaging signal of a viral RNA segment affect the packaging efficiency of the other viral RNA segments in the progeny virus particles (15).…”
supporting
confidence: 79%
“…Importantly, no progeny virus particles contain more than eight RNPs (11). Recent 3D analyses using electron tomography (ET) showed that the eight RNPs arranged in the aforementioned "seven plus one" configuration differ in length (12,13) (Fig. 1C).…”
mentioning
confidence: 97%
“…However, in our study, the MO-HA EN M EN and MO-HA EN viruses exhibited replication capacities similar to those of MO and EN viruses, suggesting that packaging-signal contributions outweigh the benefits of a possible spherical budding phenotype. In addition, electron tomography did not reveal any significant morphological difference between the parental MO and EN viruses (43,44).…”
Section: Discussionmentioning
confidence: 84%
“…We and others hypothesized that selective packaging of the eight vRNAs into an influenza viral particle might involve direct base-pairing interactions between the packaging signals (22,28,43,44). Recently, we showed that, in vitro, all MO genomic vRNA segments are involved in a single network of intermolecular interactions involving regions located at both ends of the vRNAs, suggesting that selective packaging of vRNPs is mediated by intermolecular RNA-RNA interactions (43).…”
Section: Discussionmentioning
confidence: 99%
“…Local secondary RNA structures are also believed to play a role in the packaging process of the eight vRNP complexes into progeny virions. Interactions between such RNA secondary structures may mediate the interaction between the eight vRNPs, leading to the observed 7+1 arrangement of vRNPs within budding virions as visualized by EM (22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%